Determination of tree height based on tree crown using algorithm derived from UAV imagery / Suzanah Abdullah ... [et al.] - Abdullah, Suzanah; Tahar, Khairul Nizam; Abdul Rashid, Mohd Fadzil; Osoman, Muhammad Ariffin (2021)
A single tree crown extraction is of great importance for forest management and inventory. In this study, an automated segmentation method that is able to fully utilize the unmanned aerial vehicle (UAV) data for extracting, and characterizing a single tree crowns with many geometric and topological properties. UAV becomes one of the appearance technologies that offers an affordable, cheaper, and faster technology in acquiring data for numerous applications. This technology had provided the ability to clearly look at a single tree, which shows opportunities in many activities such as monitoring, tree species mapping and tree disease mapping. In this study, UAV technology has been taking a look at several algorithms for estimating tree height value of a single tree crown. The single tree crown was obtained from the digital surface model by using four algorithms such as watershed segmentation, object based image analysis, inverse watershed segmentation and seed generation. As a conclusion, this study has contributed to the knowledge extension in this area and presented the result of the tree height values according to the segmentation algorithm at the different flying height data.